Pseudomemberanous Colitis following Cesarean Delivery with Adjunctive Intracolonic Vancomycin - Farahnaz Sadat Ahmadi; Zahra Rezaee; Fatemeh Davari Tanha; Sepideh Nekuie; Soleiman Abbasi; Sara Abbasi (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2016)
Background: Pseudo membranous colitis is a rarely reported condition in obstetrics. The clinical presentation varies from a self-limiting diarrhea to a severe pseudo membranous colitis with toxic megacolon and subsequent death. The process of this disease is mainly associated with prior antibiotic intake.  Case presentation: A 32 year-old, G4L4RIV woman was admitted 3 days after her delivery with severe diffuse abdominal pain and distention. The patient had intravenously cefazolin after cord clamping. The colonoscopy showed pseudo membranous colitis. She was managed conservatively and after 12 days of medical treatment the patients was discharged in a good condition.  Conclusion: In the patients with low grade fever, abdominal distention and diarrhea after delivery, pseudo membranous colitis should be considered a possible diagnosis in order initiate the treatment as soon as possible.